Prevalence of Pressure Injury in Inpatients at H. Adam Malik Hospital Medan in 2020-2022 - Regina, Christanti; Arwina Dalimunthe, Dina; Siregar, Irma Sepala Sari; Kamal Kharrazi Ilyas (Talenta Publisher, 2024)
Background: Pressure injury is a frequently occurring health issue in healthcare environments, especially within hospitals. The risk is increased in hospital settings where patients are frequently confined to beds or wheelchairs. Objectives: This study evaluated the prevalence of pressure injury in regular inpatients at H. Adam Malik Hospital, Medan, from 2020 to 2022. Methods: This study employs a descriptive design with a cross-sectional research approach, describing all variables using secondary data from patient medical records. Results: The research findings indicate that the most common age group is 41-60Â years old (28,4%), with females comprising the majority (52,9%). The primary diagnoses related to the occurrence of pressure injury is neurological disorders (25.5%). The most frequent location of injury is the buttocks region (45.1%), and the most prevalent stage of injury is stage III (36.3%), with the most common management approach being debridement (43.6%). Conclusion: In H. Adam Malik Hospital, Medan, from 2020 to 2022, pressure injury was mostly found at ages 41-60 years old, in women, the most prevalent underlying primary disease was neurological disorders, on the buttocks region, at stage III, and the most common management approach being debridement. Latar Belakang: Ulkus Dekubitus merupakan masalah kesehatan yang sering terjadi di lingkungan perawatan kesehatan, terutama di rumah sakit. Risiko ini meningkat di rumah sakit yang pasiennya sering terbaring di tempat tidur atau kursi roda. Tujuan: Mengetahui gambaran Ulkus Dekubitus pasien rawat inap reguler di RSUP H. Adam Malik Medan pada tahun 2020 - 2022. Metode: Penelitian ini merupakan studi deskriptif dengan rancangan penelitian cross-sectional yang seluruh variabel dilihat menggunakan data sekunder berupa rekam medis pasien. Hasil: Penelitian ini menunjukkan bahwa kelompok usia yang paling banyak adalah usia 41-60 tahun (28,4%), dengan mayoritas adalah perempuan (52,9%). Diagnosis utama yang berhubungan dengan terjadinya Ulkus Dekubitus adalah gangguan neurologis (25,5%). Lokasi ulkus yang paling sering adalah daerah bokong (45,1%), dan derajat ulkus yang paling banyak terjadi adalah stadium III (36,3%), dengan penatalaksanaan yang paling banyak dilakukan adalah debridemen (43,6%). Kesimpulan: Di RSUP H. Adam Malik Medan pada tahun 2020 hingga 2022, Ulkus Dekubitus umumnya dijumpai pada usia 41-60 tahun, wanita, diagnosis utama gangguan neurologis, lokasi bokong, derajat III, dan tata laksana debridemen.